The prevalence of foot ulcers in diabetic patients in Pakistan: A systematic review and meta-analysis - Sohail Akhtar; Aqsa Ali; Sadique Ahmad; Muhammad Imran Khan; Sajid Shah; Fazal Hassan (Frontiers Media S.A., 2022)
We aimed to determine the pooled prevalence of diabetic foot ulcers in Pakistan. MEDLINE (PubMed), Web of Science, Google scholars, and local databases were systematically searched for studies published up to August 10, 2022, on the prevalence of foot ulcers among diabetic patients in Pakistan. Random-effects meta-analysis was used to generate summary estimates. Subgroup analysis and meta-regression models were used to address the issue of high heterogeneity. Two authors independently identified eligible articles, collected data, and performed a risk of bias analysis. Twelve studies were included in the meta-analysis (14201, range 230-2199, diabetic patients), of which 7 were of "high" quality. The pooled prevalence of diabetic foot ulcers was 12.16% (95% CI: 5.91-20.23%). We found significant between-study heterogeneity (I2 = 99.3%; p < 0.001) but no statistical evidence of publication bias (p = 0.8544). Subgroup meta-analysis found significant differences in foot ulcer prevalence by publication year and by the duration of diabetes. An increasing trend was observed during the last two decades, with the prevalence of diabetic foot ulcers being the highest in the latest period from 2011 to 2022 (19.54%) than in the early 2000 s (4.55%). This study suggests that the prevalence of diabetic foot ulcers in Pakistan is relatively high, with significant variation between provinces. Further study is required to identify ways for early detection, prevention, and treatment in the population.